The Importance Of Preserving Language As Cultural Heritage - Yen Aryni; Ahmad Laut Hasibuan; Yugi Diraga Prawiyata; Kumala Sari; Harianto II; Mariana Mariana (LPPM Universitas PGRI Sumatera Barat, 2024)
The importance of preserving language as cultural heritage is a critical issue in today's globalized world. As the world becomes more interconnected, the diversity of languages is facing significant challenges that threaten their survival. This paper aims to explore the significance of preserving language as a cultural heritage and the various strategies that can be employed to ensure its survival. The study begins by examining the current state of language endangerment and the factors contributing to this situation, such as globalization, urbanization, and the influence of new technologies. The paper then discusses the role of languages in shaping a person's identity and the importance of intergenerational language transmission in preserving linguistic diversity. To address the challenges faced by endangered languages, the paper proposes several strategies for language preservation, including: 1. Developing a writing system: A writing system is essential for standardizing and teaching the language, as well as for preserving the language in print and electronic media. 2. Creating educational materials: Developing a variety of educational materials, such as textbooks, workbooks, and online resources, can help promote language learning and maintenance. 3. Establishing institutions: Creating institutions dedicated to language preservation, such as language schools, libraries, and museums, can provide a framework for language education and research. 4. Promoting cultural exchange: Encouraging cultural exchange programs, such as language classes, workshops, and festivals, can help raise awareness about the importance of language preservation and foster a sense of pride in the local culture. 5. Implementing government policies: Governments can play a crucial role in preserving languages by implementing policies that support language education, heritage preservation, and the use of indigenous languages in administration and commerce. In conclusion, preserving language as cultural heritage is essential for maintaining linguistic diversity and cultural identity. By implementing these strategies, communities and governments can work together to ensure the survival of endangered languages and promote a more culturally rich and diverse world.